PERBANDINGAN EFEKTIFITAS KOMPRES AIR HANGAT DAN KOMPRES ALOE VERA TERHADAP PENURUNAN SUHU TUBUH PADA ANAK DEMAM DI PUSKESMAS DELI TUA KEC. DELI TUA KAB. DELI SERDANG TAHUN 2020 - Nurul Aini Siagian; Andayani Boang Manalui; Mutiara Dwi Yanti; Khairatul Hikmah (Fakultas Kebidanan Institut Kesehatan Deli Husada, 2021)
Fever is a condition that is often encountered in everyday life, everyone has experienced fever, especially in children whose bodies are still susceptible to disease. Data at Puskesmas Deli Tua Kec. Deli Tua Kab. Deli Serdang from January to November 2019, there were 2,758 diseases with early symptoms of fever such as typoids, Acute Respiratory Infection (ISPA), and Dengue Fever (DH). This study aimed to determine the comparison of the effectiveness of warm water compresses and aloe vera compresses on reducing body temperature of fever children at Deli Tua Health Center. This study is quantitative research with a quasi-experimental method and uses a pre-test-post-test design with two comparison treatments. This study used population of 30 fever children in Deli Tua Health Center. Sample divided in 2 groups of 6 people each, used a purposive sampling method. Data analyzed by dependent T test and independent T test. The results showed that there was a comparison of the effectiveness of decreasing body temperature, the mean of warm compresses was 36.733°C and aloe vera was 37.983°C (0.001<0.05). Suggestions for health services from this research can be used as an easy and beneficial complementary medicine for children with fever.